An experimental investigation on the rate of CO2 absorption into aqueous methyldiethanolamine solutions - Benamor, A.; Aroua, M.K. (Korean Journal of Chemical Engineering, 2007)
In this paper, the CO2 absorption rates into aqueous solutions of Methydiethanolamine (MDEA) at various concentrations of 1, 2, 3 and 4 M and temperatures varying from 293 to 323 K were measured by using a laboratory stirred reactor. The kinetics experiments were conducted under a pseudo first order regime. The data were analyzed by means of chemical absorption theory and the kinetic parameters associated with the reaction, such as the reaction order and the reaction rate constants, were evaluated. The effect of temperature on the reaction rate constant was assessed and the activation energy was evaluated at about 44.12 kJoule/mol.